Sea Cucumber Viscera Processed by Protease Hydrolysis Combined with Cordyceps militaris Fermentation Protect Caco-2 Cells against Oxidative Damage via Enhancing Antioxidant Capacity, Activating Nrf2/HO-1 Pathway and Improving Cell Metabolism - Rui Mi; Zhiyu Fu; Jingwei Jiang; Shan Gao; Xiaoyan Guan; Xuda Wang; Zunchun Zhou (MDPI AG, 2024)
Excessive reactive oxygen species (ROS) may lead to oxidative damage and metabolic disorder. The pathogenesis of human bowel inflammation is closely related to oxidative damage of intestinal epithelial cells caused by ROS. This study aimed to explore the high-value utilization of the byproducts of sea cucumber in antioxidant food for colitis prevention. The technology of protease hydrolysis combined with Cordyceps militaris fermentation was used to obtain fermented sea cucumber viscera protease hydrolysates (FSVHs). The results revealed that FSVH could enhance antioxidant capacity and alleviate oxidative damage and apoptosis by activating the Nrf2/HO-1 pathway and triggering the self-protection immune mechanisms. Moreover, the FSVH supplementation could upregulate antioxidant-related metabolic pathways of Caco-2 cells such as glutathione metabolism, confirming the enhanced antioxidant capacity of damaged cells. In summary, FSVH could exert protective effects on Caco-2 cells in response to oxidative damage, providing a promising prospect for sea cucumber resource utilization and colitis prevention.